2016
DOI: 10.1016/j.jpowsour.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of catalyst layer defects on local membrane degradation in polymer electrolyte fuel cells

Abstract: Aiming at durability issues of fuel cells, this research is dedicated to a novel experimental approach in the analysis of local membrane degradation phenomena in polymer electrolyte fuel cells, shedding light on the potential effects of manufacturing imperfections on this process. With a comprehensive review on historical failure analysis data from field operated fuel cells, local sources of iron oxide contaminants, catalyst layer cracks, and catalyst layer delamination are considered as potential candidates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 61 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…3 Chemical degradation mechanisms typically involve the formation of radical chemical species, such as hydroxyl (HO•), hydroperoxyl (HOO•), and hydrogen (H•) radicals, which attack the backbone and/or side chain of the polymeric membrane molecule leading to its bond cleavage. [30][31][32] Mechanical degradation mechanisms are driven by mechanical stresses that develop within the constrained membrane due to dynamic hygrothermal conditions present during automotive duty cycles.…”
mentioning
confidence: 99%
“…3 Chemical degradation mechanisms typically involve the formation of radical chemical species, such as hydroxyl (HO•), hydroperoxyl (HOO•), and hydrogen (H•) radicals, which attack the backbone and/or side chain of the polymeric membrane molecule leading to its bond cleavage. [30][31][32] Mechanical degradation mechanisms are driven by mechanical stresses that develop within the constrained membrane due to dynamic hygrothermal conditions present during automotive duty cycles.…”
mentioning
confidence: 99%
“…Along with the results of OCV and FER measurements, the cross‐sectional images of the MEAs confirm that the membrane of hBN0_MEA was severely degraded after the OCV hold test for 100 h (Figure c–f). After the ASTs, all of the membranes of the MEAs did not suffer from delamination, or mechanical cracks (Figure d,f). However, the thickness of hBN0_MEA is reduced by 30% to 31.6 ± 2.3 µm, while the thickness of hBN1_MEA hardly changed even after the AST (≈44.3 µm).…”
Section: Resultsmentioning
confidence: 99%
“…Real defects and their effect on cell performance are very difficult for PEMFC manufacturers to characterize once the fuel cell stacks are installed. The topic of real defects in PEMFC electrodes is currently the subject of debate and is not fully understood …”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that local variations in the thickness of the CCM and GDL originating during MEA fabrication can lead to cracks that function as stress concentrating points in the membrane and ultimately cause pinholes to form . Fewer studies have focused on CL defects developed due to deformation of membrane and fabrication of CCMs, that ultimately increases the electrical resistance of the CL and decreases overall performance in PEMFC.…”
Section: Introductionmentioning
confidence: 99%